Fluid Removal With Ultrasound Guided Protocol Improves the Efficacy and Safety of Dehydration in Post-Resuscitated Critically Ill Patients: A Quasi-Experimental, Before and After Study. Issue 4 (October 2018) - Wang, Luhao; Qiu, Chunfang; Guan, Xiangdong; Chen, Minying; Chen, Juan; Si, Xiang; Du, Zhicheng; Liu, Yanqiu; Ouyang, Bin
Abstract : ABSTRACT: Fluid overload is associated with increased morbidity and mortality in critically ill patients. However, researches rarely study the precise start or end point of fluid removal and no protocol was developed to control the fluid removal process. We hypothesized that individualized fluid removal with ultrasound-guided protocol could improve the efficacy and safety of fluid removal in post-resuscitated critically ill patients. A quasi-experimental, before and after trial was conducted to identify the benefits of ultrasound-guided fluid removal. Fluid removal was performed either following the doctor's experience in Control group, or abiding the ultrasound guided protocol in Ultrasound group. The study end points were the start time, end time, length of fluid removal, and the complications related to fluid removal. A total of 85 subjects were finally analyzed in this study. The fluid removal was started earlier, completed quicker and ended earlier (21.0 ± 14.6 h vs. 35.1 ± 26.5 h, 49.8 ± 32.6 vs. 93.0 ± 42.8 h, 69.0 ± 32.2 h vs. 126.4 ± 52.5 h, P < 0.05) in Ultrasound group than in Control. The subjects had more daily negative fluid balance and urine output (−990.4 ± 636.1 mL vs. −723.6 ± 549.5 mL, 2425.8 ± 886.7 mL vs. 1560.7 ± 1125.3 mL, P < 0.05) in Ultrasound group. The time of lung B-lines to reduce to zero was shorter and B-line at the end point was less (49.5 ± 36.6 h vs. 75.6 ± 58.8 h, 0[1] vs. 0[0], P < 0.05) in Ultrasound group. The length of intensive care unit stay in shock subgroup had a tendency to shorten (96.1 ± 61.5 h vs. 174.6 ± 132.0 h, P > 0.05) in Ultrasound group. We concluded that fluid removal with individualized ultrasound-guided protocol improves the efficacy and safety of dehydration in critically ill patients.